2012
DOI: 10.1111/j.1365-2222.2012.04012.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring neutrophils and platelets during casein‐induced anaphylaxis in an experimental BALB/c mouse model

Abstract: On the basis of our data we suggest that in addition to mast cells and basophils, neutrophils and platelets participate in the anaphylactic response in this BALB/c mouse model. Platelet and neutrophils expressing relevant immunoglobulin receptors may therefore have a synergistic effect with allergen specific IgE as well as IgG antibodies in food-induced anaphylaxis. We suggest that management of these cells could be of clinical importance to handle anaphylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The drop of leukocytes upon allergen challenge in the mouse study is in accordance with a previous observation in anaphylaxis, [31] but opposed the results from the human allergic subjects in our study, where peripheral leukocyte counts significantly increased after allergen challenge. A subset analysis showed that human segmented neutrophils and to some extent basophils accounted for the total leukocyte elevation, without relevant changes in less matured neutrophils or eosinophils.…”
Section: Discussionsupporting
confidence: 90%
“…The drop of leukocytes upon allergen challenge in the mouse study is in accordance with a previous observation in anaphylaxis, [31] but opposed the results from the human allergic subjects in our study, where peripheral leukocyte counts significantly increased after allergen challenge. A subset analysis showed that human segmented neutrophils and to some extent basophils accounted for the total leukocyte elevation, without relevant changes in less matured neutrophils or eosinophils.…”
Section: Discussionsupporting
confidence: 90%
“…Murine studies have also studied platelets and erythrocytes response during anaphylaxis and have suggested possible participation via an allergic mechanism 18, 19. Specifically platelet's had a significant drop during anaphylaxis in the murine study by Krishnamurthy et al 18.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the role of neutrophils in the liver, following nanomaterial exposure has not been addressed previously, however, it has been shown that nautrophils can accumulate within hepatic microvasculature, following increase in inflammatory mediators such as TNF-α, IL1, MIP-2 and PAF [23,24]. Furthermore, in a recent study, an increase in numbers of neutrophils in the liver of BALB/c mice was observed during anaphylaxis [25].…”
Section: Resultsmentioning
confidence: 98%